The Influence of Stress, Discipline and Environment on Employee Performance in Emporio Architects Bali - Larassati Prasetyaning HARUM; I.B. Agung DHARMANEGARA; A.A. Ketut JAYAWARSA (Loka: Journal Of Environmental Sciences, 2023)
Purpose:This research examines and analyzes the influence of work stress, work discipline and work environment on employee performance.Methodology:This research was conducted at Emporio Architect Bali with a sample of 57 respondents, who were taken using saturated sampling techniques. All data obtained from the distribution of the questionnaire is suitable for use. The data was then analyzed using multiple linear regression and hypothesis testing (t-test and f-test).Findings:The research results show that work stress, discipline and environment positively and significantly affect employee performance at Emporio Architect Bali. Work stress negatively and significantly affects employee performance at Emporio Architect Bali.Implication:It means that the more work stress increases, the more employee performance at Emporio Architect Bali decreases. Work discipline positively and significantly affects employee performance at Emporio Architect Bali. It means that the more work discipline increases, the more employee performance at Emporio Architect Bali will increase. The work environment positively and significantly affects employee performance at Emporio Architect Bali. It means that the better the work environment is, the more employee performance at Emporio Architect Bali will increase.